2017
DOI: 10.1016/j.bbadis.2017.02.012
|View full text |Cite
|
Sign up to set email alerts
|

A novel mechanism of diabetic vascular endothelial dysfunction: Hypoadiponectinemia-induced NLRP3 inflammasome activation

Abstract: It has been well documented that hypoadiponectinemia is associated with impaired endothelium-dependent vasodilation. However, the exact molecular mechanism which mediates this process has not been fully described. The current study aimed to investigate the role of hypoadiponectinemia-induced NLRP3 inflammasome activation in diabetic vascular endothelial dysfunction and its molecular mechanism. Male adult adiponectin knockout mice and wild type mice were fed with a high fat diet to establish a type 2 diabetic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 46 publications
2
40
0
2
Order By: Relevance
“…Thus, it is conceivable that FSTL1 levels may not only reflect the MU state, but may also activate the NLRP3 inflammasome in macrophages infiltrating VAT, thereby resulting in an MU state with more adverse inflammatory profiles as mediators of increasing metabolic risk. Furthermore, low levels of adiponectin from adipocyte showing the FSTL1 as a marker of metabolic unhealth inverse correlation with the cardiovascular disease [30] also induced activation of the NLRP3 inflammasome [31,32]. Taken altogether, these findings indicate that additional investigations to identify the relationships between adiponectin and FSTL1 are necessary.…”
Section: Discussionmentioning
confidence: 88%
“…Thus, it is conceivable that FSTL1 levels may not only reflect the MU state, but may also activate the NLRP3 inflammasome in macrophages infiltrating VAT, thereby resulting in an MU state with more adverse inflammatory profiles as mediators of increasing metabolic risk. Furthermore, low levels of adiponectin from adipocyte showing the FSTL1 as a marker of metabolic unhealth inverse correlation with the cardiovascular disease [30] also induced activation of the NLRP3 inflammasome [31,32]. Taken altogether, these findings indicate that additional investigations to identify the relationships between adiponectin and FSTL1 are necessary.…”
Section: Discussionmentioning
confidence: 88%
“…We and others reported the increased superoxide anion production, lipid peroxidation, and NADPH oxidase activity in the plasma and tissue of type 2 diabetic mice . It is well established that oxidative stress is involved in the development and progression of diabetes mellitus and diabetic complications.…”
Section: Discussionmentioning
confidence: 61%
“…The study of our laboratory also found that anthocyanin protected against diabetes-related endothelial dysfunction [16]. On the other hand, hypoadiponectinemia-induced in ammasome activation may be the molecular mechanism for diabetic vascular endothelial dysfunction [19]. Basic and clinical studies have identi ed the anti-atherogenic function of adiponectin [20] and its positive effect on vascular in ammation and endothelial function [21].…”
Section: Possible Mechanismmentioning
confidence: 71%